2016
DOI: 10.1111/jtxs.12224
|View full text |Cite
|
Sign up to set email alerts
|

Structure influence on mechanical and acoustic properties of freeze‐dried gels obtained with the use of hydrocolloids

Abstract: The research is expected to show the phenomenon of structure formation when preparing and freeze-drying gels and explain the influence of the process parameters (time of aeration, the type of hydrocolloids) on the formation of the internal structure and physical properties of a dried product, especially mechanical and acoustic properties. This achievement will contribute to the development of the science of food and human nutrition, especially within the context of the popular research on aerated diet products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 61 publications
(63 reference statements)
3
7
0
Order By: Relevance
“…This can also be explained by the results of the previous tests, since the denser and thinner structure of these discs confers better mechanical properties. Other authors report that freeze-dried gels become harder the larger the pore diameter [53], and as can be seen in Figure 8, this is also true in our case, since the reference disc (H batch) withstands the most force before breaking and also has the highest pore diameter.…”
Section: Swelling Behavioursupporting
confidence: 85%
“…This can also be explained by the results of the previous tests, since the denser and thinner structure of these discs confers better mechanical properties. Other authors report that freeze-dried gels become harder the larger the pore diameter [53], and as can be seen in Figure 8, this is also true in our case, since the reference disc (H batch) withstands the most force before breaking and also has the highest pore diameter.…”
Section: Swelling Behavioursupporting
confidence: 85%
“…The internal structure of the freeze-dried broccoli gel was delicate, porous, which is certainly influenced by the air bubbles introduced into the gel mass while mixing the gel components ( Figure 7). Similar results were obtained Ciurzyńska et al [83] and Ciurzyńska et al [84], who studied the structure of freeze-dried gels based on a mixture of xanthan gum and locust bean gum of various compositions, and also showed that structure is porous, with variable sized pores due to the cracking of numerous air bubbles. Porosity is very important for the quality and the texture of dry foods, because has a significant effect on the physical, and mechanical properties of foods [90].…”
Section: Properties Of Dried Gels and The Effect Of Different Ingredisupporting
confidence: 85%
“…Such a low value indicates the microbiological safety of the freeze-dried gel, and with the activity of water below 0.2, enzymatic reactions are also inhibited [100]. The obtained value is similar to the water activity of freeze-dried gels with a mixture of xanthan gum and locust bean gum powder, where, depending on the aeration time, aw of 0.018-0.021 was obtained [84] and significantly lower than the water activity of freeze-dried agar gels with apple purée (0.148-0.151) [101]. The addition of hydrocolloid to thawed vegetables should not reduce water activity, as was demonstrated by Hoefler [102], who claimed that gums are substances that retain water, but do not reduce its activity by its high molecular weight, while the addition of a larger amount of hydrocolloid may affect the reduction of water activity of the product.…”
Section: Properties Of Dried Gels and The Effect Of Different Ingredisupporting
confidence: 67%
See 2 more Smart Citations